Customized fenestrated endovascular graft repair of abdominal aortic aneurysm with concomitant horseshoe kidney. (June 2014) - Brown, Kai; Robinson, David; Bray, Alan
The occurrence of an abdominal aortic aneurysm (AAA) with horseshoe kidney (HSK) is an uncommon but complex surgical problem. This report outlines three such cases, the particular issues encountered and how customized endovascular grafts were successfully used to overcome them. Case one shows an accessory renal artery arising from the left common iliac artery, case two shows a right accessory renal artery from the AAA sac and case three has the right renal artery coming off the distal abdominal aorta within the sac. Across three patients, each graft had a single custom fenestration, which preserved a total of three major vessels with no change in renal function. Customized endografts are a viable tool to preserve aberrant vessels and thus renal mass in AAA and HSK. Customized endografts require an extensive work-up and are currently expensive to fabricate. However they are rapidly evolving as a mainstream tool in vascular surgery and provide a solution in cases of aberrant visceral vasculature.